Football: Drill Increasing Method Passing Ability - Nurwahidin Hakim; Wahyuni Ulpi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to improve passing skills by using the drill method in class X SMAN 2 Palopo. This research includes classroom action research. The research subjects were class X students of SMAN 2 Palopo, with a total of 30 students, consisting of 10 boys and 20 girls in the 2021/2022 academic year. The meetings in this study were designed in two cycles, namely cycle I and cycle II. Passing data collection was carried out using passing assessment process sheets in cycles I and II. The collected data were analyzed quantitatively. The results of the quantitative analysis of the passing data show that the number of students who passed in cycle I was 22 students with a percentage of 73% and the number of students who passed in cycle II was 29 people with a percentage of 97%. The results of the qualitative analysis show that there is a significant increase in passing. Based on the results of data analysis, it was concluded that there was an increase in passing ability using the drill method.